2019
DOI: 10.1101/611806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A highly responsive pyruvate sensor reveals pathway-regulatory role of the mitochondrial pyruvate carrier MPC

Abstract: Mitochondria generate ATP and building blocks for cell growth and regeneration, using pyruvate as the main substrate. Here we introduce PyronicSF, a user-friendly GFP-based sensor of improved dynamic range that enables real-time subcellular quantitation of mitochondrial pyruvate transport, concentration and flux. We report that cultured mouse astrocytes maintain mitochondrial pyruvate in the low micromolar range, below cytosolic pyruvate, which means that the mitochondrial pyruvate carrier MPC controls the dec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…increase in cytosolic lactate, revealing the presence of abundant surface lactate transporters in these cells ( Figure 6B). This result is consistent with the previous results achieved with a single-fluorophore indicator for pyruvate 34 representative environment. We also performed a transport assay that proved that this highly responsive indicator displays better responses and is, therefore, more suitable to set up transport assays in multiwell plate readers for high-throughput screening.…”
Section: Superfusion Of Acutely Isolated Brains With Lactate Resultedsupporting
confidence: 93%
See 2 more Smart Citations
“…increase in cytosolic lactate, revealing the presence of abundant surface lactate transporters in these cells ( Figure 6B). This result is consistent with the previous results achieved with a single-fluorophore indicator for pyruvate 34 representative environment. We also performed a transport assay that proved that this highly responsive indicator displays better responses and is, therefore, more suitable to set up transport assays in multiwell plate readers for high-throughput screening.…”
Section: Superfusion Of Acutely Isolated Brains With Lactate Resultedsupporting
confidence: 93%
“…Superfusion of acutely isolated brains with lactate resulted in a quick and reversible increase in cytosolic lactate, revealing the presence of abundant surface lactate transporters in these cells (Figure 6B). This result is consistent with the previous results achieved with a single-fluorophore indicator for pyruvate 34 . These experiments show the suitability of the lactate indicator to explore lactate dynamics in ex vivo preparations from different model systems.…”
Section: Lactate Dynamics In Ex Vivo Preparations Of Drosophila Melanogaster Larval Brainssupporting
confidence: 93%
See 1 more Smart Citation
“…If pyruvate is not dehydrogenated to lactate or taken up by the mitochondria and converted to acetyl-coA, gluconeogenesis can occur with excess carbon stored as glycogen for times of bioenergetic stress, however, this process is tightly regulated. Using emerging fluorophore sensor technology, a recent study suggested that mitochondria in cultured mouse astrocytes can maintain lower levels of pyruvate compared to the cytosol [20].…”
Section: Astrocyte Metabolismmentioning
confidence: 99%
“…2c,d). The EC 50 values of Green Lindoblum and Green Pegassos are lower than previously developed indicators 2,3,8 , and therefore, they would be appropriate to monitor changes in the minimal level of intracellular lactate and pyruvate. Hill coefficient for Green Lindoblum and Green Pegassos was 1.2 and 1.4, respectively, suggesting that these indicators are applicable for an appropriate range of lactate and pyruvate levels.…”
mentioning
confidence: 93%